On the Duty of Excellence - Labarriere, Pierre-Jean (1999)
The Greek term apntí. art of moderation, strategy of happiness, is a fundamental attitude not addressed by the mere "moral" connotation of the terms merit and virtue. It defines, instead, a leve! of excellency reconciliating the interior and the exterior. theory and praxis, knowledge and action. Far from any hard stoicism, virtue is a force in movement; it translates if necessary the human capacity of "changing circumstances. "As a true road of sense displayed "with and for others" (Ricoeur), virtue assumes a poietic dimension expressed by a certain power of creation, where not only the individual but also the political are at stake.